2020
DOI: 10.1515/biol-2020-0094
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles: synthesis, characterisation and biomedical applications

Abstract: Nanotechnology is a rapidly growing field due to its unique functionality and a wide range of applications. Nanomedicine explores the possibilities of applying the knowledge and tools of nanotechnology for the prevention, treatment, diagnosis and control of disease. In this regard, silver nanoparticles with diameters ranging from 1 to 100 nm are considered most important due to their unique properties, ability to form diverse nanostructures, their extraordinary range of bactericidal and anticancer properties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(108 citation statements)
references
References 184 publications
(201 reference statements)
0
71
0
Order By: Relevance
“…We biosynthesized AgNPs using the natural extract of B. tomentosa Linn. We then applied various biophysical and biochemical methods to characterize the potential biomedical applications of the AgNPs [ 8 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 86 ] and validated their antimicrobial and antioxidant properties [ 87 , 88 ]. We also evaluated a possible mechanism of action via molecular docking analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We biosynthesized AgNPs using the natural extract of B. tomentosa Linn. We then applied various biophysical and biochemical methods to characterize the potential biomedical applications of the AgNPs [ 8 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 86 ] and validated their antimicrobial and antioxidant properties [ 87 , 88 ]. We also evaluated a possible mechanism of action via molecular docking analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles are structures with dimensions ranging from approximately 1 to 100 nm that exhibit significantly different physical (mechanical, optical, electrical) and chemical properties when compared with their larger counterparts [ 6 , 7 ]. Over the past 10 to 20 years, metal nanoparticles, and AgNPs in particular, have attracted attention due to their versatility and broad range of industrial and biomedical applications [ 8 , 9 , 10 , 11 ]. Potential uses include antimicrobial (antibacterial, antifungal, and antiviral) agents [ 12 , 13 , 14 , 15 , 16 , 17 ], biomedical device coatings, drug-delivery carriers, and imaging probes for diagnostic and optoelectronic applications [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, AgNPs play roles primarily in non-conventional and enhanced biomedical applications such as wound dressing, drug delivery, tissue scaffoldings and proactive coating applications. In this regard, the AgNPs are considered to possess intrinsic features such as attractive chemical and physical functionality, non-toxic nature, wide spectrum of bactericidal properties, anticancer properties, and therapeutic abilities [15]. Hence, the applicability of AgNPs have increased in nanotechnology, biomedicine, and environment, thus there is a need for development of cost-effective method for the biosynthesized AgNPs [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the enormous potential of nanotechnologies in biomedicine for the diagnosis and treatment of a wide range of human diseases [1] . Silver nanoparticles (AgNPs) are crucially signi cant in nanomedicine because of their appealing physicochemical properties, high antimicrobial capability and low toxicity, speci c capacity to establish versatile nanostructures, and low manufacturing costs [2] . Compared to other metal nanoparticles such as gold, zinc and copper, silver nanoparticles are far less toxic to mammalian cells.…”
Section: Introductionmentioning
confidence: 99%